2001
DOI: 10.1021/jp010144f
|View full text |Cite
|
Sign up to set email alerts
|

A Density Functional Study on the Effect of the Trans Axial Ligand of Cobalamin on the Homolytic Cleavage of the Co−C Bond

Abstract: Density functional theory (DFT) Becke3LYP calculations including full and restricted geometry optimizations are carried out on the complexes [Co(Cor)(Benz)(CH 3 )] (Cor ) corrin, Benz ) benzimidazole), [Co(Cor)(Benz)], [Co(Cor)(CH 3 )], and [Co(Cor)]. These systems, despite the absence of side-chains, constitute the most realistic models used to date for DFT calculations on cofactor B 12 and its homolysis product. The calculations prove that both thermodynamics and kinetics of the homolytic bond cleavage of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
105
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(123 citation statements)
references
References 61 publications
15
105
0
Order By: Relevance
“…As in previous studies, [25][26][27] DFT gives satisfactory geometries for alkyl corrins (Table 1). For the methyl adduct, the Co-C distance is short, 1.96 Å, as it is in MeCbl (1.98 Å) 37 while the bond to the axial imidazole is long, 2.22 Å, as is the Co-dimethylbenzimidazole bond in MeCbl (2.16 Å).…”
Section: Alkyl Corrinssupporting
confidence: 83%
“…As in previous studies, [25][26][27] DFT gives satisfactory geometries for alkyl corrins (Table 1). For the methyl adduct, the Co-C distance is short, 1.96 Å, as it is in MeCbl (1.98 Å) 37 while the bond to the axial imidazole is long, 2.22 Å, as is the Co-dimethylbenzimidazole bond in MeCbl (2.16 Å).…”
Section: Alkyl Corrinssupporting
confidence: 83%
“…All geometric optimizations were made to the default tolerances of Gaussian. Previously, DFT calculations have been made [23][24][25][26][27] for R-Cbl(III) compounds; however, there had been no calculations for the one-electron reduced products, the CH 3 -Cbl(II) species. Actually, this radical anion does not appear to have much Co(II) character since the singly occupied MO (SOMO) for the doublet species is mostly a corrin ring p * MO with only a little d yz character.…”
Section: Electronic Structure Calculationsmentioning
confidence: 99%
“…Density functional theory (DFT) calculations provided valuable insight into the structure and catalytic properties of adenosylcobalamin [19][20][21][22]. The Co-C bond dissociation energy of coenzyme B 12 has been estimated to be about 30 kcal/mol from DFT studies [23][24][25][26][27][28][29][30][31][32][33], which is in good agreement with experimental results [34,35]. QM/MM calculations of glutamate mutase [36] and methylmalonyl-CoA mutase [37,38] showed that the bond dissociation energy of the Co-C bond in the enzymes is significantly reduced by the geometrical distortion of the coenzyme.…”
Section: Introductionmentioning
confidence: 99%